Order-Parameter Model for Synergetic Theory-based Railway Freight System and Evolution in China - Feng, Fenling; Yang, Liuen; Lan, Dan (Promet - Traffic&Transportation, 2013)
We investigate the synergetic nature and complexity of the railway freight system and select 13 parameters (railway fixed asset investment, GDP, railway’s revenue kilometers, etc.) as the system’s state variables. By using method of least square and method of external function, we build an order-parameter model for synergetic theory-based railway freight system, which will potentially support the studies on the railway freight system’s evolution. Our result shows that railway fixed asset investment is the order-parameter that governs the evolution of railway freight system: the average random fluctuation parameter is 0.7060, which means that the mean fluctuation period of railway freight system is 9 years. Evolution of the railway freight system is a gradual process with abrupt changes from time to time.